Heart rate variability responses to a psychologically challenging scuba dive - Flouris, A. D.; Scott, J. M. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM: Given the controversy regarding cardiovascular responses and heart rate variability (HRV) in underwater conditions, the authors assessed the combined effect of psychological stress and scuba diving on cardiac autonomic modulation measured through HRV during and following a diving mission. METHODS: Ten healthy adults (three females; seven males; Body Mass Index [BMI] 23.7±2.1; age 26.4±2.9) performed a 20-minute dive in a neutral buoyancy water tank (27 °C) at a depth of five meters. The dive scenario involved repairing components of a scientific instrument using a high fidelity task mock-up. Data for HRV (three from the time domain and three from the frequency domain) were obtained for 20 minutes prior to (PRE), during (DIVE), and for 20 minutes following (POST) the dive sortie. RESULTS: Heart rate in DIVE was increased when compared to PRE and POST (74±10 vs. 108±16 vs. 72±8 beats.min-1, respectively). The time domain measure pNN50 (37.3±16.9 vs. 14.1±10.1 vs. 22.0±12.2%, respectively), and the R-R interval (0.72±0.26 vs. 0.59±0.11, vs. 0.86±0.24, respectively) showed a significant decrease in DIVE compared to PRE and POST, while no changes were detected in the frequency domain indices between measurements. During POST, the square root of the mean of squared differences between successive intervals returned to PRE levels, but pNN50 values remained decreased at DIVE levels. CONCLUSIONS: These findings suggest a decrease in parasympathetic indices during a psychologically challenging scuba dive and a delay in vagal reactivation during the 20-minute period following the dive.